Pemikiran Hadis di Indonesia (Studi Analisis Terhadap Pemikiran Nahdlatul Ulama) - Wely Dozan; M. Dani Habibi (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2020)
This article examines NU which is an organizational structure among Muslims who have trends in applying Islamic law. One of the foundations of the Nahdlatul  Ulama in establishing Islamic law has never been separated from the context of the Qur'an, Hadith, Ijma 'of the Companions and Qiyas. So the outline in taking the source of Islamic law is related to the hadith problem which is made as a reference in the sense of Nu in using hadith as the legal basis for four schools, moreover the usual lower hadith, dha'if hadith is used as a source search method law. Taking in the community often discussed the system of extracting Islamic legal sources. We will analyze this short article by analyzing the methods that are used at the same time in order to find out the hadiths used in applying the source of Islamic. The results of this study show that the hadith in the perspective of NU scholars is as a reference to Islamic law and that the hadith has a strong blasphemy based on the study of sanad, matan, and rawi as well as the quality and quantity of hadith based on methods in attributing Islamic law.Keywords: NahdlatulUlama, Hadith, Method.